Reliability of near-infrared spectroscopy for measuring intermittent handgrip contractions in sport climbers - Balas, J.; Kodejska, J.; Krupkova, D.; Hannsmann, J.; Fryer, S. (The Journal of Strength and Conditioning Research, 2018)
The use of near-infrared spectroscopy (NIRS) to investigate muscle oxygenation changes during physical tasks such as rock climbing has rapidly increased within recent years; yet, there is no known measure of reliability. The current study aimed to determine intersession reliability and minimal detectable change (MDC) of continuous wave NIRS parameters during intermittent handgrip contractions in rock climbers. Thirty-two sport climbers were tested for exhaustive intermittent handgrip exercise (8-second contraction-2-second relief) at 60% of maximal voluntary contraction on 3 separate days. During each visit, continuous wave NIRS was used to determine tissue saturation index (TSI) as the measure of tissue oxygenation in the flexor digitorum profundus. To assess the intersession reliability, the intraclass correlation coefficient (ICC), SEM, coefficient of variation (CV), and MDC were used. Mean deoxygenation during the contractions provided reliable results ([INCREMENT] TSI; first trial -8.9 ± 2.9%, second trial -8.8 ± 2.7%, and third trial -8.4 ± 2.6%; ICC = 0.692; SEM = 1.5%; CV = 17.2%; MDC = 4.2%). Mean muscle reoxygenation during the relief periods was similarly reliable ([INCREMENT] TSI; first trial 9.0 ± 3.1%, second trial 8.8 ± 2.9%, and third trial 8.5 ± 2.7%; ICC = 0.672; SEM = 1.7%; CV = 19.0%, MDC = 4.7%). As such, continuous wave NIRS provides a reliable measure of deoxygenation and reoxygenation during intermittent contractions to failure in the forearm flexors of rock climbers. Differences exceeding ~4.5% for [INCREMENT] TSI during contraction and relief periods should be considered meaningful.